Android-based Application for Depression, Anxiety, and Stress Screening - Endriyani, Sri; Susanti, Eva (Poltekkes Kemenkes Palu, 2024)
The escalating issue of emotional and mental disorders, such as stress, anxiety, and depression, necessitates proactive measures to anticipate adverse effects on individuals experiencing them. One of the ways is by implementing a screening method. An android-based screening application can offer immediate feedback about an individual’s mental health condition. This study employs a research and development approach encompassing the preliminary study, model development, and model validation. The outcome of this study was an initial design for an Android-based screening application, DeAs Care, which aims to measure the levels of depression, anxiety, and stress in individuals. The DeAs Care application underwent evaluation by a group of 15 adolescent participants, all between the ages of 18 and 20. The assessment employed a Likert scale with a range of 1 to 5. The results indicated an overall satisfaction rate of 85%, corresponding to a ‘Very Good’ rating. The application was utilized on 216 adolescent participants to evaluate their levels of depression, anxiety, and stress. The assessment results indicate that the subsequent proportions of participants received a diagnosis of depression: 21% of the participants reported experiencing mild depression, while 20% showed moderate depression. Additionally, 8% had severe depression, and 6% had extremely severe depression. The other 45% of participants indicated they were in normal conditions. As for the participants' anxiety levels, the results of the assessments showed that 15% of them had mild anxiety, 31% had moderate anxiety, 23% had severe anxiety, 16% had extremely severe anxiety, and 15% of them were in a normal state. Furthermore, concerning stress levels, the study found that 20% of individuals had mild stress, 24% experienced moderate stress, 6% experienced severe stress, and 1% experienced extremely high stress levels. In comparison, the remaining 50% reported normal stress levels. The findings indicate that utilizing the DeAs Care Android application for screening adolescent mental health is an effective method for preventing issues related to mental and emotional disorders through self-assessment.